Information Seeking, Sharing and Use on Religion among Afghan youth in Toronto - Quirke, Lisa (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This poster summarizes the findings of a qualitative, exploratory study on Afghan youth’s information seeking, sharing and use regarding religion. Data collection included interviews and participant observation. Findings included the key role of technology, the iKoran and social networking sites in particular, in facilitating information seeking and sharing on Islam. Cette affiche résume les résultats d’une étude qualitative exploratoire auprès des jeunes femmes afghanes sur leurs pratiques de recherche, de partage et d’utilisation de l’information concernant la religion. Les données recueillies proviennent d’entrevues et d’observation des participantes. Les résultats démontrent le rôle clé de la technologie, iKoran et les sites de réseautage social en particulier, et facilite la recherche et le partage d’information sur l’Islam.